Within the State and Without the Nation: Unraveling the Nation-State’s Dual Role in the Lives of Migrant Descendants Through Sayad’s Critical Sociology - SAJIR, ZAKARIA; Molinero-Gerbeau, Yoan (Italian Sociological Review, 2025)
This article examines the dual identity challenges of migrant descendants within the system of immigration built by nation-states, drawing on Abdelmalek Sayad’s critical sociology of migration. It highlights the tension between their status as legally recognised citizens and culturally marginalised ‘others’. The discussion underlines the nation-state’s struggle to reconcile its homogeneous national identity ideals with the realities of global migration, often failing to integrate these individuals fully. Central to this analysis is the distinction between ‘state’—legal-political institutions—and ‘nation’—cultural-linguistic identities. This division places migrant descendants in a liminal space, navigating their dual identities as insiders and outsiders. The article critiques the conventional integration paradigm that places the onus of assimilation on these individuals, suggesting that nation-states should instead adapt their structures for true inclusivity. The paper calls for reevaluating the nation-state, proposing a more inclusive and pluralistic approach to national identity that acknowledges the layered identities of all citizens, especially migrant descendants. This reconfiguration aims to ensure their full participation in the nation-state’s social, cultural, and political life. By shifting the responsibility to nation-states, the article aligns with Sayad’s critique of migration policies, emphasising the need for structural reforms that transcend legal recognition to achieve genuinely inclusive practices. This approach is vital for addressing the disparities and tensions within contemporary nation-states and moving towards a more equitable society.